China's aid & soft power in Africa : the case of education & trai ning - King, Kenneth, 1940- (Woodbridge, Suffolk ; Rochester, NY : James Currey, Boydell & Brewer Ltd, 2013)
China's increasing role as an education and Human Capital donor in A frica, and the significance of this, both economically and politically.
Includes bibliographical references (p. [215]-228) and index.
Keywords: Education -- Africa -- Finance; Educational assistance, Chinese -- Africa; China -- Foreign economic relations -- Africa; Africa -- Foreign economic relations -- China; China -- Foreign relations -- Africa; Africa -- Foreign relations -- China